Nuclear energy and economic development : causality revisited - Cheng, Shirlene Xing Yi (2015)
Numerous studies have been conducted to examine the relationship between nuclear energy consumption and economic growth but such empirical research does not include a complete data set and time frame. In this study, we aim to examine the relationship among 28 countries that utilized nuclear energy within a multivariate panel framework from 1965 to 2012. These countries are divided into three panels: high-income countries, upper-middle-income countries and lower-middle-income countries. Johansen’s Fisher panel cointegration test reveals that there exists one cointegrating equation between real GDP, nuclear energy consumption (NEC), real gross fixed capital formation (GFCF) and labor force participation rate (LABOR). The results from Granger causality test shows unidirectional causality from nuclear energy consumption to economic growth in the short-run and long-run for high-income countries. Whereas for the upper-middle-income countries, GDP, GFCF and LABOR have unidirectional causality to NEC in the short-run, but there is no causal effect between the variables in the long-run. For the lower-middle-income countries, NEC has no causation effect to any variables in the short-run and long-run. Thus, the results suggest that for high-income countries, nuclear energy is an important element for economic development.